Cloning, sequencing and phylogenetic analysis of omp25 gene from Brucella abortus field strain - JAIN, ANKIT; SHARMA, N S; AGRAWAL, R K; ARORA, A K (The Indian Journal of Animal Sciences, 2013)
The present study was carried out to clone, sequence and analyze complete omp25 gene of Brucella abortus field strain. The primers for omp25 gene of Brucella abortus were designed and sites for NcoI and XhoI were inserted in the forward and reverse primers, respectively. PCR amplification resulted in an amplicon of 693bp. The amplified product was cloned in TA cloning vector. One positive clone named Brucella omp25/3 was subjected to sequencing and the data obtained were analyzed. Sequencing data exhibited an orf of 693bp. The deduced orf of omp25 gene was submitted to NCBI (Accession No. JQ839278.1). The cloned omp25 gene sequence shows high degree of homology with subject sequences available in the NCBI database. Codon based test of neutrality indicated that natural selection or purifying selection was operating on the omp25 sequences and test of homogeneity indicated that the evolution of sequences through same pattern was homogeneous except for Brucella species CCM 4916 (AM712384). Evolutionary divergence of nucleotide sequence indicated that omp25 gene sequence has less genetic variability among divergent species, which signifies that omp25 is highly conserved among different species of Brucella. Therefore omp25 gene can be used for development of recombinant antigen based immunological assays, subunit or DNA vaccine as well as for detection and differentiation of the pathogen by polymerase chain reaction.